Big Data's Call to Philosophers of Education - Blanken-Webb, Jane (Philosophical Inquiry in Education, 2017)
This paper investigates the intersection of big data and philosophy of education by considering big data’s potential for addressing learning via a holistic process of coming-to-know. Learning, in this sense, cannot be reduced to the difference between a pre- and post-test, for example, as it is constituted at least as much by qualities of experience as it is the situation, process of inquiry and its consequences. Long a perennial concern of philosophers of education, the author suggests that big data offers a budding opportunity for philosophers to engage in dialogue with empirical research in order to better understand the process of learning as coming-to-know. Drawing on John Dewey’s theory of inquiry and his philosophy of experience, the author demonstrates ways that both empirical and philosophical research stands to benefit from cross-dialogue. In offering an unprecedented glimpse of empirical detail, the author proposes that big data stands to afford new insights into this most complex human process and that Dewey’s philosophy offers a vital lens of interpretation that can help philosophers of education to make use of this data in addressing the perennial question of how humans come-to-know.